Corporate explorer : how corporations can beat startups at the innovation game - Binns, Andrew (Managing principal); O'Reilly, Charles A.; Tushman, Michael (John Wiley & Sons, Inc., 2022)
"The probability of failure in corporate innovation outside of a firm's core business is staggeringly high. Yet, the vast majority of existing books about innovation focus on startups and their entrepreneurs, methodologies, and ecosystems. Few, if any, focus on corporate innovation, those leaders who champion it, and how to maximize their chances of success. Corporate Explorer fills this gap. In January 2021 alone, there were over 10,000 Google searches for business innovation. Innovation is as much about method, strategy, organization, and culture, as it is about leadership and individual leaders. At the center of every story of corporate innovation is a 'Corporate Explorer' who dares to go where others do not, a leader capable of closing the gap between knowing what needs to be done to grow new businesses and actually doing so. We are living in a time of unparalleled disruption that has been heightened by Covid-19 and the digital revolution that is taking place across industries. Managers see these opportunities and know that firms that innovate during times of crisis are more successful in the long term than those that do not. This book gives them practical guidance for how they can act on these instincts, help their firms succeed, and grow their own careers."--